Information for contributors and readers for issue 4-2017 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Pursuant to the decision given in Article 27, paragraph 1, point 4, and in accordance with the acquired opinion given in Article 25, paragraph 1, point 5 of the Act on Scientific and Research Activities (Official Gazette of the Republic of Serbia, No 110/05, 50/06-cor and 18/10), the Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Techncal Courier for the years 2015 and 2016.